2017
DOI: 10.1051/0004-6361/201628706
|View full text |Cite
|
Sign up to set email alerts
|

Keplerobservations of the asteroseismic binary HD 176465

Abstract: Binary star systems are important for understanding stellar structure and evolution, and are especially useful when oscillations can be detected and analysed with asteroseismology. However, only four systems are known in which solar-like oscillations are detected in both components. Here, we analyse the fifth such system, HD 176465, which was observed by Kepler. We carefully analysed the system's power spectrum to measure individual mode frequencies, adapting our methods where necessary to accommodate the fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 113 publications
(126 reference statements)
0
35
0
Order By: Relevance
“…The shaded region represents the expected dispersion due to the range of masses and metallicities within the sample (e.g., the two high points are lower metallicity stars, giving them thinner convection zones that reach the critical Rossby number at faster rotation rates). The asteroseismic rotation rates and ages for a ∼3 Gyr-old solar analog binary system (White et al, 2017) have been overplotted, validating asteroseismic rotation measurements and the age scale for sun-like Kepler stars. A few well-characterized solar analogs are shown with yellow points, including 18 Sco (Petit et al, 2008;Li et al, 2012;Mittag et al, 2016), α Cen A (Bazot et al, 2007;Bazot, Bourguignon, and ChristensenDalsgaard, 2012), and 16 Cyg A & B Creevey et al, 2017).…”
Section: Breakdown Of Magnetic Brakingmentioning
confidence: 54%
“…The shaded region represents the expected dispersion due to the range of masses and metallicities within the sample (e.g., the two high points are lower metallicity stars, giving them thinner convection zones that reach the critical Rossby number at faster rotation rates). The asteroseismic rotation rates and ages for a ∼3 Gyr-old solar analog binary system (White et al, 2017) have been overplotted, validating asteroseismic rotation measurements and the age scale for sun-like Kepler stars. A few well-characterized solar analogs are shown with yellow points, including 18 Sco (Petit et al, 2008;Li et al, 2012;Mittag et al, 2016), α Cen A (Bazot et al, 2007;Bazot, Bourguignon, and ChristensenDalsgaard, 2012), and 16 Cyg A & B Creevey et al, 2017).…”
Section: Breakdown Of Magnetic Brakingmentioning
confidence: 54%
“…In another, study soon to appear, Themeßl et al (2017) present a reanalysis of KIC 8410637 from the full 4 years of Kepler photometry and extended spectroscopic monitoring and present a detailed analysis of KIC 6540750 and KIC 9540226. On the main sequence, several binary stars have been analysed, such as KIC 7510397 (Appourchaux et al 2015), KIC 10124866 (White et al 2017) or the system of 16 Cyg A&B (Metcalfe et al 2015;Davies et al 2015) in which both components are oscillating. The red-giant or sub-giant primaries of only few binary systems, Procyon, θ 1 Tau, µ Herculi, were studied with seismology through the groundbased observations, utilising high-resolution spectroscopy with a meter-per-second accuracy (Arentoft et al 2008;Beck et al 2015b;Grundahl et al 2017, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Hjørringgaard et al (2017) have reported on discrepancies between constraints from different independent methods when determining the parameters of the very well-studied red giant HD 185351. Moreover, the problem of an unconstrained α MLT is not unique to red giants: White et al (2017) showed that their parameter determinations using changed significantly when α MLT was free to vary compared to a fixed solar value.…”
Section: Introductionmentioning
confidence: 99%